Synthesis and Post‐Polymerization Modification of Poly(N‐(4‐Vinylphenyl)Sulfonamide)s. Issue 10 (3rd May 2021) - Molle, Edgar; Mutlu, Hatice; Theato, Patrick
Abstract: Herein, a straightforward synthesis of a novel class of polymers, that is, poly( N ‐(4‐vinylphenyl)sulfonamide)s, and their monomers is reported. A set of monomers with varying electron densities, fine‐tuned by different substituents on the aromatic sulfonamide moiety, is polymerized by free radical polymerization featuring low molar masses (2300 ≤ M n ≤ 3200 g mol −1 ) and low dispersities (1.15 ≤ Đ ≤ 1.47). Further, the post‐polymerization modification of the obtained polymers via aza‐Michael addition with electron‐deficient alkenes is demonstrated using organic superbases as catalysts, paving the way toward the facile synthesis of novel polymeric protected β‐amino acid derivatives. Abstract : A novel class of styrene‐derived sulfonamide‐based polymers (aromatic poly( N ‐(4‐vinylphenyl)sulfonamide)s) is prepared in a straightforward fashion by free radical polymerization of their respective monomers. The inherent secondary amine functionality of the sulfonamide motif is used as post‐polymerization modification handle via aza‐Michael addition with electron‐deficient alkenes resulting in polymeric protected β‐amino acid derivatives.